Il Palio di San Michele di Bastia (Umbria): un nuovo modello festivo - Fiorella Giacalone (EtnoAntropologia)
Bastia is a small town in Umbria; in recent decades it has become a great commercial and industrial development, with the presence of so many immigrants. The Palio di San Michele, from 50 years, is the city festival, which takes place during one week in September, with sports competitions, theater performances, the "lizza" (the relay game). Bastia is not a major city, it is not a destination for cultural tourism, but the Palio represents in an exemplary way as a festival can "create" a community, a place of gathering of young and adolescents. Analyzing some festive models, the essay reflects on new perspectives for the study of the festival, with an emphasis on new categories of festival in relation to the territorial identity.